Penerapan Model Pembelajaran Kooperatif Tipe TAPPS (Thinking Aloud Pairs Problem Solving) Dalam Meningkatkan Hasil Belajar Mahasiswa - Silvana Enjelina Bander (Journal on Education, 2023)
Cooperative Learning in Higher Education is a response to various challenges that students have to face in society, including the demand to work together or team work both in business sectors, as well as to uncertain changes in the development of information technology. The purpose of this research is to improve students' economic mathematics learning outcomes through group learning of the Thinking Aloud Pairs Problem Solving (TAPPS) type. Improving student learning outcomes and activities was examined in a classroom action research, which was divided into two learning cycles and the TAPPS model was applied to learning. The research subjects were semester 1 students, majoring in Accounting/Management, class A in the afternoon, academic year 2022 – 2023. The number of students in class A was 30 people. From the results of the initial test, before the implementation of TAPPS the average student score was 67.67 with a passing presentation of 20%, that is, only 6 people passed the initial test. Then student learning outcomes changed in cycle 1, obtained an average score of 74.67 with a passing percentage of 43%, namely 13 people. Then student learning outcomes increased in cycle 2, with an average score increasing to 77.83 with a passing percentage of 77% or as many as 23 people. The conclusion is that the use of the TAPSS model can improve student learning outcomes.